NURSING CARE PROVIDED TO PATIENTS WITH ASTROCYTOMA AND MININGIOMA TUMORS: Literature narrative review - Soares e Silva, Maria Aparecida (2024)
The nursing care provided to patients with astrocytoma and meningioma tumors is importante to guarantee a comprehensive and humanized approach during the treatment of these brain pathologies. The objective of this study is to analyze the role of nurses in caring for patients with astrocytoma and meningioma, seeking to identify the main challenger faced and effective intervention strategies. To achieve this objective, a bibliographical review of scientific articles, books and documents related to the topic will be carried out, in order to theoretically support nursing practices aimed at these patients. The expected results include the description of the most pertinent nursing  care, the importance of education and support for patients and families, in addition to the identification of possible gaps in the care provided. It is concluded that the role of nurses is fundamental in monitoring patients with astrocytoma and meningioma, contributing significantly to improving quality of life and the effectiveness of treatment. It is essential that the nursing team is trained and dedicated to providing holistic and individualized care, always aiming for the patient's well-being and recovery.